THE ROLE OF CAUSE-RELATED MARKETING ON MULTINATIONAL CORPORATE REPUTATION, BRAND IMAGE, AND PURCHASE INTENTION IN INDONESIA AND THAILAND (Study Case on The Body Shop Against Animal Testing Campaign) - Alanna Alia Hannantyas; Edy Yulianto; M. Kholid Mawardi (Fakultas Ilmu Administrasi Universitas Brawijaya, 2016)
Saat ini, perusahaan multinasional bersaing untuk memenangkan hati para pelanggan di berbagai negara. Dalam era globalisasi ini, ada banyak cara untuk mendapatkan perhatian pelanggan dan pemasaran adalah suatu keharusan untuk dilakukan. Banyak perusahaan barat yang mempraktikan Cause-Related Marketing (CRM). Sebaliknya, di Asia khususnya di negara-negara Asia Tenggara CRM dapat dianggap sebagai sesuatu hal yang baru. Oleh karena itu, penelitian ini dilakukan untuk menguji peran Cause-Related Marketing pada reputasi perusahaan multinasional, citra merek dan intensitas pembelian di Indonesia dan Thailand. Data yang diperoleh kemudian diuji dengan data survei kuantitatif primer yang dikumpulkan dari 113 responden di Indonesia dan Thailand. Analisis jalur digunakan untuk menguji hiphotesis. Temuan menunjukkan bahwa Cause-Related Marketing memiliki efek positif pada variabel seperti: reputasi perusahaan multinasional, citra merek dan niat beli. Kata Kunci : Cause-Related Marketing, Reputasi Perusahaan, Citra Merek, Intensitas Pembelian ABSTRACT Today,‘MNCs’are competing‘hard to win customers’ heart‘in many partsiof the world. In this globalization era, there are many way’to get customers’ attentions and marketing is a must thing to do. Many western companies are practicing Cause-Related Marketing (CRM). On the contrary, in Asia specifically in Southeast Asian countries CRM can be considered as new. Therefore, this study aims to examine the role of Cause Related Marketing on multinational corporate reputation, brand image and purchase intentions in Indonesia and Thailand. The conceptualization was then tested with primary quantitative survey data collected from 113 respondents in Indonesia and Thailand. Path analysis was used to test the key hyphothesis. The findings showed that Cause-Related Marketing has a positive effect on multinational corporate reputation, brand image and purchase intention. Keywords : Cause-Related Marketing, Corporate Reputation, Brand Image, Purchase Intention